Students examining textiles - Unidentified photographer (Colorado State University. Libraries, 2018)
Photograph of students examining textiles from the collection during a class in 2018. Textiles are laid out on tables while students gather around them.
Keywords: Fashion -- History; Fashion -- Exhibitions